Volume 2B: Turbomachinery 2018
DOI: 10.1115/gt2018-76992
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Impact of Span-Wise Flow Distribution on the Performance of a Mixed Flow Turbine

Abstract: Current trends in the automotive industry towards engine downsizing means turbocharging now plays a vital role in engine performance. A turbocharger increases charge air density using a turbine to extract waste energy from the exhaust gas to drive a compressor. Most turbocharger applications employ a radial inflow turbine. However, to ensure radial stacking of the blade fibers and avoid excessive blade stresses, the inlet blade angle must remain at zero degrees. Alternately, mixed flow turbines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Morrison et al 10 found that a flow cone angle of 95 resulted in a small efficiency improvement while an angle of 65 resulted in greater losses. Meanwhile Lee et al 11 found a performance benefit with a reduction in cone angle but a change in MFP meant the efficiency benefits were not directly comparable. Lee et al argued that the misalignment of the flow with the rotor nozzle-less area in the study by Morrison et al 10 could be responsible for the differing conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison et al 10 found that a flow cone angle of 95 resulted in a small efficiency improvement while an angle of 65 resulted in greater losses. Meanwhile Lee et al 11 found a performance benefit with a reduction in cone angle but a change in MFP meant the efficiency benefits were not directly comparable. Lee et al argued that the misalignment of the flow with the rotor nozzle-less area in the study by Morrison et al 10 could be responsible for the differing conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that reducing the flow angle towards the hub side of the passage resulted in an efficiency improvement of 1% relative to a baseline case with a uniform distribution. A further study on the impact of inlet flow angle distributions on MFT rotor performance was conducted by Lee et al [13]. This study imposed five different spanwise flow velocity profiles at the inlet to a numerical model of a MFT rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison et al [12] and Lee et al [13] have demonstrated that MFT performance can potentially be improved by altering the flow conditions at rotor inlet. However, the results of these studies were obtained by imposing the desired flow angle distributions and total pressure and temperature conditions directly upstream of the rotor leading edge.…”
Section: Introductionmentioning
confidence: 99%
“…It was found the tilted volute could increase both the steady-state performance [10] and the cycle-averaged performance under pulsating working conditions [11]. A follow-up study investigated the effect of inlet spanwise flow distributions on the aerodynamic performance by implementing different distributions on a radial and a tilted stator layouts [12]. However, a direct comparison of those two stator layouts was not achievable due to the lack of aerodynamic similarity [12].…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study investigated the effect of inlet spanwise flow distributions on the aerodynamic performance by implementing different distributions on a radial and a tilted stator layouts [12]. However, a direct comparison of those two stator layouts was not achievable due to the lack of aerodynamic similarity [12]. Morrison et al [13] investigated the effect of inlet flow cone angle on the performance of an MFT, as an indirect way to investigate the stator endwall tilting designs.…”
Section: Introductionmentioning
confidence: 99%